Antinociceptive and anti-inflammatory activities of a Chinese herbal recipe (DJW) in animal models - P. Kunanusorn (2018)
Since in our previous study, Duhuo Jisheng Wan (DJW), which means pill of pubescent angelica root and mulberry mistletoe combination, demonstrates clinically comparable efficacy to diclofenac in the symptomatic treatment of osteoarthritis (OA) of the knee after 4 weeks of treatment. Therefore, in order to verify its mechanisms of action, this study was performed to investigate the antinociceptive and anti-inflammatory activities of DJW in various animal models. The antinociceptive activity of DJW was investigated by using the formalin test in mice model. The acute inflammatory model using the carrageenin-induced hind paw edema in rats and the chronic inflammatory model using the cotton pellet-induced granuloma formation in rats were utilized. Results showed that DJW possessed a marked antinociceptive activity in both phases of the formalin test in mice. However, in the carrageenin-induced hind paw edema model, which is known to be sensitive to cyclooxygenase (COX) inhibitors, DJW showed an insignificant anti-inflammatory effect, and in the cotton pellet-induced granuloma model, it had no antigranuloma formation and showed no effect on the transudate weight. In addition, DJW showed no suppressive effects on weight gain and the thymus weight of the rats. In conclusion, the overall results demonstrate that DJW possess both central and peripheral antinociceptive activities. However, its anti-inflammatory activity, if any, could not be demonstrated in these two inflammatory models in the present study and remains to be elucidate. Industrial relevance: Since drug therapy in OA patients, such as paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs), and topical analgesics may prove ineffective in some patients, and long-term therapy with NSAIDs often have been associated with serious adverse effects. Such patients are turning increasingly to herbal medicines and DJW may be an alternative since it demonstrates clinically comparable efficacy to diclofenac in the symptomatic treatment of OA of the knee after 4 weeks of treatment in our previous study. The present study would help clarifying its mechanism(s) of action. With this additional information, it would be helpful for the industry to produce herbal formulation with known mechanism of action, less side effects, and has clinically comparative efficacy to conventional medicine in the symptomatic treatment of OA of the knee. © 2009 Healthy Synergies Publications.